(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2013)
The so called Ninfeo of Nora, roman city nearby Cagliari, was discovered in the Fifties. During the 10 years of archaeological excavation very few documentation was collected. The excavation and the restoration towards the end of the Sixties have been carried out to make the site accessible as a resource for tourism: works have been made to search for scenographyc structures, without caring about their stratigraphic value and to give the mosaics visibility in situ. This is the reason why the pavements were risen, restored and recollocated or the lacunas were filled with cement. To get round to this loss of information, the Università degli Studi of Milan have tried to rebuilt the evolution of the Ninfeo life, searching strips of pavement and plaster that haven’t been touched by the works for the conservation, and mapping the building in the context of the area, using total station and CAD.